An Examination of the Socio-Economic Determinants of Punishment Using Abductive Polynomial Networks - Hakeem, Farrukh Behzad (1996)
The purpose of this research is to examine aspects of the relationship between socio-economic conditions and imprisonment in a particular historical setting. Previous research suggests that this relationship is problematic and situationally variable. The approach taken in this dissertation reflects a belief that earlier studies can be faulted for their failure to take account of the fiscal climate of the state as an influence on the size of prison populations. This analysis will employ the Marxist model, as developed by Rusche and Kirchheimer (1939) and widely applied (though with mixed results) in research conducted over the last half-century. This model will be modified according to the postulates of the model delineating the relationship between state spending and the development of capitalist society specified by O'Connor (1973). Although fiscal influences are mentioned by Rusche and Kirchheimer it has not been integrated into a research model either by these authors or those who have followed them. One important object of this research will therefore be to evaluate the usefulness of the Marxist approach to the analysis of the labor supply/imprisonment nexus, as this approach is represented by a modified and supposedly, improved version of a standard model. The project will at the same time attempt to determine the importance of fiscal factors on penal policy. Characteristics of prison populations addressed will include race. This characteristic is important here mainly as an indicator of marginality. Findings in this area will, however, be of additional value in documenting the particular impact of penal policies on minorities